293 Molecular determinants of CDK4 inhibitor activity in low-grade serous ovarian cancer. (18th September 2019) - Llaurado Fernandez, M; Hoenisch, J; Kim, H; Dawson, A; Lam, N; Cheasley, D; Gorrienge, K; Abhimanyu, N; Campbell, I; Huntsman, D; DiMattia, G; Kobel, M; et al.
Abstract : Objectives: Effective therapies for low-grade serous ovarian cancer (LGSC) patients are urgently needed. CDKN2A/B (p16) loss and hormone receptor (ER/PR) expression are well described in LGSC. We aimed to study p16-CDK4-Rb pathway status and CDK4/6 inhibitior (CDK4/6i) activity in LGSC cell lines. Methods: Protein expression of p16, CDK4, CDK6, Rb, p-Rb, CCDN1 and E2F were evaluated by western blot in 13 LGSC and 2 breast cancer (BCa) lines. Gene mutation and copy-number (CN) data on the selected candidates were obtained using whole-exome sequencing (WES) analyses. CN data on 93 LGSC FFPE tumors was also obtained. Palbociclib (CDK4/6i) effects were evaluated using IC50 assays. Results: None of the LGSC lines had detectable mutations in p16, CDK4, CDK6, Rb, p-Rb, CCDN1 or E2F genes. CDK4/CDK6 protein expression was present in all lines. Absence of p16 protein expression and CDKN2A CN loss was detected in 84.6% (11/13) LGSC cell lines. Interestingly, total and phosphorylated Rb were detected in both BCa lines, but only in 53.8% (7/13) LGSC lines. RB1 hemizygous CN loss was detected in 7.7% (1/13) LGSC lines and in 7.5% (7/93) LGSC tumors. Palbociclib had limited cytotoxic effects in the BCa and LGSC cell lines tested. Conclusions: Palbociclib mainly has cytostatic effects in LGSC in-vitro and its activity does not correlate with either p16 or CDK4 expression. About half of our cell lines showed Rb loss, likely mediated by post-translational events. Rb-proficiency is required for drug efficacy in other cancers, and may account for our observations. These results raise important considerations for clinical trial design.